Montenegro: new pro-NATO government approved (Katehon think tank. Geopolitics & Tradition, 2016)
Montenegro's parliament approved a new cabinet during the parliamentary meeting, which was attended only by the representatives of the Democratic Party of Socialists, led by former Prime Minister Milo Djukanovic, and some small parties united with them. The parties, which were representing real interests of Montenegrins, were not present in the courtroom. Thus, the new government was approved by 41 votes in the 81-seat parliament.